AUTOMATED ACCESS CONTROL SYSTEMS - KORCHYNSKYI, VOLODYMYR; TARASENKO, IRYNA; RATSYBORYNSKYI, SERHII; AKAIEV, OLEKSANDR; KHADZHYOHLO, ARTEM (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The paper provides an overview and analysis of the problems in the application of automated access control systems based on NFC. The capabilities of the Arduino platform are investigated and an access control system with an RFID-NFC module is developed on its basis. The use of automated access control systems in the modern world is becoming increasingly relevant. It involves a number of benefits that such systems can bring to businesses and other entities. These systems simplify and speed up the process of identifying a person, save time and increase the efficiency of security services, but still require human control. RFID-NFC technology is up-to-date, so the development and use of this technology for an access control system can solve the problem of unauthorized access to premises and/or controlled areas. Also, a company/enterprise can save money on identification devices, since various documents with an embedded NFC tag can be used as an identifier. For example, it can be a passport of a citizen of Ukraine, a passport of a citizen of Ukraine for travelling abroad, a certificate of registration, bank cards and a smartphone with NFC function, etc. An automated access control system is a set of advanced technologies and software designed to control and restrict access to a specific private territory/controlled area. The main purpose of an automated access control system is to ensure security, control and monitoring of access to a private territory/controlled area. Such systems are used to identify personnel, vehicles, etc. that have access to a restricted area/controlled zone. Access control systems can be integrated with other security systems, such as video surveillance systems, intrusion detection/prevention systems, etc.